Electromagnetic Signatures from Pulsar Remnants of Binary Neutron Star Mergers: Prospects for Unique Identification Using Multiwavelength Signatures - Mainak Mukhopadhyay; Shigeo S. Kimura (The Astrophysical Journal Letters)
Binary neutron star (BNS) mergers can result in the formation of long-lived magnetar remnants that can enhance neutrino and electromagnetic (EM) emissions. In this work, we study the resulting multiwavelength EM emissions and the prospects of their detectability in the current and upcoming EM telescopes. We model the pulsar-wind-nebula system where the long-lived pulsar with dipolar magnetic fields of 10 ^13 −10 ^15 G (magnetar) spins down and is surrounded by an outward-expanding nebula and kilonova ejecta. Although at early times following the merger the EM signatures are unobservable owing to heavy attenuation, they become observable on timescales of ${ \mathcal O }(1--10)$ days after the merger. We find that the survey and follow-up observations have horizon distances ≳1 Gpc for most of the wave bands and conclude that the detection prospects for such long-lived remnants in the EM channel are promising. This is of crucial importance for multimessenger observations from BNS mergers to constrain the physical parameters of the remnants. Furthermore, we highlight how observations across the EM band can uniquely identify magnetar-powered transients resulting from BNS mergers and establish concrete associations of the detected gravitational-wave signatures with such transients.